2014
DOI: 10.3349/ymj.2014.55.4.1058
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Osteoporosis of Prescriber According to Level of Medical Institute

Abstract: PurposeThere are gaps between the treatment guideline and clinical practice of osteoporosis showing low compliance. Although attitude and knowledge of prescriber have been known to be associated with the low compliance in real clinical practice, no study has assessed the knowledge of prescriber regarding osteoporosis in accordance to the level of medical institution. We compared the knowledge on osteoporosis of general practitioners with that of practitioners in a tertiary referral hospital.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…[ 40 42 ] In this study, we also evaluated the influence of the level of institutions where the SERMs were prescribed on the subsequent fracture risk, but no significant difference was found. This is in line with the previous reports by Yoon et al [ 43 ] where the knowledge on osteoporosis of prescribers were not related to the level of medical institute. As osteoporotic fracture risk and the knowledge for treatment does not vary among the level of institutions, patients need not be treated from higher level of medical institutions expecting for higher treatment outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…[ 40 42 ] In this study, we also evaluated the influence of the level of institutions where the SERMs were prescribed on the subsequent fracture risk, but no significant difference was found. This is in line with the previous reports by Yoon et al [ 43 ] where the knowledge on osteoporosis of prescribers were not related to the level of medical institute. As osteoporotic fracture risk and the knowledge for treatment does not vary among the level of institutions, patients need not be treated from higher level of medical institutions expecting for higher treatment outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies using FOOQ reported that most physicians, another healthcare provider rather than nurses, did not answer correctly in item 14 (“walking has a great impact on bone health”). [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 17 18 ] We modified 2 (item 10 and 15) among the 20 items, according to recent epidemiologic studies from Korean and recommendation by Korean Society for Bone and Mineral Research. [ 1 20 ] In modified item 10, the residual lifetime risk of osteoporotic fractures was about 60% in Korean women older than 50 years. [ 1 ] In modified item 15, the recommendation of daily calcium intake was 1,200 mg/day for the Korean population.…”
Section: Methodsmentioning
confidence: 99%
“…Lack of recognition and knowledge of orthopedic surgeon for the osteoporotic fracture may be one of the reasons. 11 21 22 23 24 25) Sorbi and Aghamirsalim 25) reported that the typical orthopedic surgeon is not inclined to manage patients with osteoporotic fracture appropriately due to lack of knowledge in comparison with internist, which raised questions concerning their role in the management of osteoporosis. Several reports suggested that awareness of orthopedic surgeon reduces the risk of osteoporotic fracture and education is the way to improve management for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%